Analisis Kesesuaian Kalender Jawa Islam dengan Kalender Hijriyah - Sholehuddin, Muhammad; Siti Tatmainul Qulub (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2022)
Before Islam came, Javanese people were familiar with the calendar system. The influx of HinduBuddhist influences also influenced the calendar in Java. Then with the start of the establishment of an Islamic-style kingdom on the island of Java, especially during the Islamic Mataram period when the influence of Islam entered the island of Java, the calendar system was changed by the great sultan to a Javanese calendar using Islamic calendar calculations. The Javanese calendar is still in existence so it is necessary to know the adjustments that occur between the Saka calendar and the Hijri calendar which then produces the Javanese Islamic calendar and to know the application used to determine the beginning of the Qomariah month with the aim of knowing howto use the Javanese Islamic calendar and know its application in determining the beginning of themonth of Qomariah. The calculation system used in the Javanese Islamic calendar is the Urfi reckoning system, except in certain years where there are different long and short year appointments at certain times. Based on the results of the analysis, it is concluded that the adjustments of the Javanese Islamic calendar in the calculations are intended to maintain conformity with the hijri calendar.Keywords: Javanese Calendar, Islamic Calendar, Qomariah Calendar